Naturally Ambivalent: Religion's Role in Shaping Environmental Action - Vaidyanathan, Brandon (Sociology of religion, 2018)
This article examines the role of religion in shaping environmental action by bringing contemporary arguments in cultural sociology to bear on longstanding debates about the role of religion in environmental care. Drawing on 169 in-depth interviews from 22 Christian, Muslim, and Jewish congregations in Houston and Chicago, we examine conditions under which religion enables and constrains environmental action. Findings reveal that religious institutions can motivate members’ environmental actions when they cultivate not only declarative environmental beliefs but also nondeclarative environmental practices. Religion may inhibit environmental concern when respondents believe environmental commitment undermines their religious beliefs, but such justifications are disconnected from the actual environmental practices they nevertheless engage in. We also find that religious individuals largely attribute motivations for their environmental action to institutions other rather than religion. Our findings shed new theoretical light on the mixed results that characterize research on religion and the environment.